Coffee and tea consumption and glioma risk: a meta-analysis of cohort studies - Jinyu Pan; Chuan Shao; Hui Tang; Nan Wu (Frontiers in Nutrition)
BackgroundResearch on the association between glioma risk and coffee and tea consumption remains inconclusive. This study seeks to present a meta-analysis of the relationship between coffee and tea intake and glioma risk.MethodRelevant cohort studies that collected coffee and tea exposure prospectively were identified through searches of the PubMed, Embase, and Scopus databases. Eligible studies included those providing adjusted relative risk estimates or hazard ratios (HRs) with 95% confidence intervals (CIs), or data sufficient for such calculations. Study quality was evaluated using the Newcastle-Ottawa Scale, while the GRADE system assessed the quality of evidence. The analysis explored glioma risk concerning the highest versus lowest levels of coffee and tea intake, supplemented by a dose–response evaluation using a one-stage robust error meta-regression model.ResultsA total of nine studies, published between 2004 and 2020, were included. In a model comparing the highest and lowest levels of coffee and tea consumption, 3,896 glioma cases were identified among 2,648,468 participants. Correspondingly, the pooled HRs with 95% CIs were 0.98 (0.87–1.09) for coffee and 0.95 (0.86–1.06) for tea, respectively. Furthermore, no evidence of publication bias was detected for either beverage. The dose–response analysis indicated a near “L”-shaped relationship between tea consumption and glioma risk, with the most notable risk reduction observed in individuals consuming more than 2.5 cups of tea per day. However, additional tea intake beyond this threshold did not confer evident risk reduction. According to Grade scoring system, the quality of meta-evidence was classified as “very low” for coffee and “low” for tea.ConclusionThis meta-analysis provides evidence suggesting a potential inverse association between tea consumption and glioma risk, while no such association was observed for coffee consumption. Given that the evidence for coffee was classified as “very low” and for tea as “low,” cautious interpretation of the findings is warranted, and further research is needed to validate these results.